Перспективи подальшого вдосконалення міжнародної системи одиниць SI - Павленко, Юрій Федорович; Голікова, Катерина Валеріївна (НТУ "ХПІ", 2015)
В статті наведено перспективи подальшого вдосконалення Міжнародної системи одиниць, проект перевизначень ампера, кельвіна, моля, кілограма, секунди, метра, кандели через ФФС, а також шляхи створення природного еталона маси. Розглядаються наслідки перевизначення основних одиниць на подальший розвиток квантової метрології. Найважливішим наслідком нової системи буде позбавлення від останнього артефакту – прототипу кілограма і перехід на його природне визначення.

Prospects of further improvement of the International system of units, the project of redefinition of ampere, kelvin are given in article, asking, kilogram, second, meter, candela through FFS. Acceptance of new definitions to a number of new main units will become a revolutionary step in respect of further improvement of the international system of units. Consequences of redefinition of the main units on further development quantum metrologists are considered. The most important consequences of redefinition will become: elimination of the last artifact – a prototype of kilogram and transition to its natural definition, creation of a natural standard of kilogram; elimination of dualism in definitions of electric units; specifications of values of a number of FFS that is essential to physics and science in general; creation of conditions for transition to natural system of units.
Prospects of further improvement of the International system of units of SI
Keywords: перевизначення; еталон; фундаментальні фізичні сталі; кілограм; ампер; кельвін; моль; секунда; метр; кандела; unit; redefinition; standard; kilogram; ampere; kelvin; mol; dualism; artifact